Green Library Transition in Bayelsa and Rivers States, Nigeria : Awareness and Perception of Librarians in University Libraries - Ogunbodede, Kolawole F.; Cocodia , Bulorgbamu (University of Dar es Salaam Library Journal, 2025)
The study investigates the awareness and perceptions of green library practices among librarians in university libraries in Bayelsa and Rivers States, using both quantitative and qualitative methods through surveys and interviews. Out of 76 librarians, 68 completed an online questionnaire, which was analysed through frequency counts and percentages. Statistical analysis with SPSS version 29 showed high reliability (Cronbach’s alpha of 0.87). Findings revealed a moderate awareness of green practices among librarians, who mainly rely on books, journals, online content, and colleagues for information. Institutional support for green initiatives was weak due to insufficient training, funding, and policies. Although librarians have positive views on implementing green practices, barriers include limited professional development opportunities and resistance to change. Recommendations include regular training, awareness campaigns, adoption of energy-efficient technologies, and prioritising funding for sustainable activities in university libraries. https://dx.doi.org/10.4314/udslj.v20i1.5